A pilot study of road lighting, cycle lighting and obstacle detection. (August 2017) - Fotios, S; Qasem, H; Cheal, C; Uttley, J
This paper investigates cyclists' detection of an obstacle on the surface of the road ahead, observed in peripheral vision, and how this is affected by variations in light level from road and cycle lighting. The data analysed were the height at which a rising obstacle was detected, this simulating an approaching irregularity in the road surface. The results suggest that when cycling on a lit road, cycle lighting frequently offers no benefit for peripheral detection and may make it worse. It was demonstrated that position matters: At low illuminances, a hub-mounted lamp improved detection over a handlebar-mounted lamp. This benefit was sufficient to offset the reduction in detection found when decreasing road lighting from 2.0 lux to 0.2 lux.